2013
DOI: 10.1177/2158244013497721
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the Media in Scaling-Up HIV Testing in Kenya

Abstract: The main objective of this study was to examine the association between media exposure and voluntary counseling and testing (VCT), and factors that influenced VCT among Kenyan women and men. Retrospective cross-sectional data from Kenya Demographic and Health Survey 2003 were used, adjusting for weights and strata to account for survey complex design. The study sample comprised women aged 15 to 49 (n = 8,050) and men aged 15 to 54 (n = 3,539). Among those who read newspapers/magazines almost every day, fewer w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 34 publications
6
20
0
Order By: Relevance
“…The study further showed that women who were educated have higher odds to carry out premarital HIV testing. This finding is in line with a study conducted in Kenya [ 32 ] and Uganda [ 33 ]. This could be elucidated by educated women take care of HIV infection, as they easily understood both the transmission and prevention methods [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…The study further showed that women who were educated have higher odds to carry out premarital HIV testing. This finding is in line with a study conducted in Kenya [ 32 ] and Uganda [ 33 ]. This could be elucidated by educated women take care of HIV infection, as they easily understood both the transmission and prevention methods [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…This study noted that media, health workers and HIV campaigns remain key information sources. It is however key to note that different sub populations utilize different media channels for information, thus necessary to critically review specific channels or models before considering specific media options for any population group [ 20 ]. For example, our study noted that males were more likely to have peers as source of information while females were more likely to use media as a source of HIV information.…”
Section: Discussionmentioning
confidence: 99%
“…To address this public health issue, mass communication plays a key role (Vidanapathirana et al, 2005). In fact, mass media is an important channel to increase an individual's knowledge about sexual health, improve the knowledge of facilities related to HIV prevention and highlight the benefits of HIV testing (Onsomu et al, 2013;Sano et al, 2016). Sano et al (2016) finds that mass media increases the knowledge of HIV and facilities related to HIV testing and creates a demand for HIV testing.…”
Section: Introductionmentioning
confidence: 99%